2014
DOI: 10.1186/s12888-014-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

Triggers of suicide ideation and protective factors of actually executing suicide among first onset cases in older psychiatric outpatients: a qualitative study

Abstract: BackgroundSuicide is a global issue among the elderly, but few studies have explored the experiences of suicide ideation in older Asian psychiatric outpatients.MethodOlder psychiatric outpatients (N = 24) were recruited by convenience from one medical centre and one regional hospital in northern Taiwan. Participants were recruited if they met these inclusion criteria: 1) ≥65 years old, 2) without severe cognitive deficit, 3) outpatients in the psychiatric clinics at the selected hospitals, and 4) self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 36 publications
3
39
0
2
Order By: Relevance
“…The present study expands the findings of Lee et al () on suicidal ideation and protective factors of suicide in older adults. Adaptive factors are coping strategies, which can inhibit or diminish continued suicidal ideation: support from family and friends, pharmacological therapy, refocussing emotions, and religious beliefs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study expands the findings of Lee et al () on suicidal ideation and protective factors of suicide in older adults. Adaptive factors are coping strategies, which can inhibit or diminish continued suicidal ideation: support from family and friends, pharmacological therapy, refocussing emotions, and religious beliefs.…”
Section: Discussionsupporting
confidence: 89%
“…Religious activities reduced anxiety, because participants did not feel a need to be in control of their emotions. Other studies have shown religious beliefs can function as protective factors for the elderly and reduce suicidal ideation (Chen et al , Lee et al ; McClain et al ; Wu et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSII does not include some triggers of suicidal ideation reported by other older people, such as illness in oneself or family members (Lee et al ., ), death of family members/friends (Lee et al ., ), loneliness (Rurup et al ., ; Lee et al , ), and perceived burden to others (Cukrowicz et al , ). All these items were included in the initial TSII but excluded after pre‐testing in 200 older outpatients because of low item total Pearson's correlation, low internal consistency (Cronbach's α value), or ambiguous factor loading in factor analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Because depression is an important predictor of suicide among older people (Conwell and Thompson , ), construct validity was evaluated by comparing differences between TSII scores of participants with and without depressive tendency using the independent t ‐test. Based on loneliness being an important factor associated with suicide among older Taiwanese people (Lee et al ., ), criterion validity of the TSII was examined by testing the correlation coefficients of its scores with scores on both the BSSI and UCLA Loneliness Scale. Internal consistency of the TSII was assessed by estimating Cronbach's α coefficients.…”
Section: Methodsmentioning
confidence: 97%